Инженерная подготовка строительного производства - Цай Т. Н. Трофим Николаевич; Ширшиков Б. Ф. Борис Федорович; Баетов Б. И. Батыркул Исаевич; Цай В. Т. Валерий Трофимович (Москва, Стройиздат, 1990)
Исключено из фонда НТБ ТПУ